A cross-sectional study of non-suicidal self-injury in a Chinese adolescent inpatient cohort - Sun, Ke; Li, Anni; Li, Yichen; Xie, Jun; Tong, Yonghao; Ma, Jun; Wu, Yong (Frontiers in Psychiatry, 2023)
Background: The non-suicidal self-injury (NSSI) is a significant predictor of completed suicide and is increasingly recognized as a serious public health concern. Multiple factors, including social, familial, mental, and genetic factors could influence the occurrence of this behavior. Identification the early risk factors is important for screening and preventing this behavior. Methods: Here, we recruited a total of 742 adolescent inpatient participants from a mental health center and conducted a series of diagnostic interviews and questionnaires to assess NSSI behavior and other events. Bivariate analysis was used to detect differences between groups in NSSI and non-NSSI. Then, binary logistic regression was fitted to identify predictors of NSSI as a function of these questionnaire scores. Results: Of the 742 adolescents examined, a total of 382 (51.5%) participants engaged in NSSI. Bivariate analysis showed that age, gender, depression, anxiety, insomnia, childhood trauma was significantly associated with NSSI. Logistic regression results suggested that females had 2.43 higher odds of engaging in NSSI when compared to their male counterparts (OR = 3.43, 95%CI = 2.09 - 5.74, p-value = 1.70×10-6). Depression was a primary risk predictor for NSSI with each additional increase in symptoms of depression increased the odds of engaging in NSSI by 18% (OR = 1.18, 95%CI = 1.12 - 1.25, p-value = 2.25×10-8). Conclusions: More than half of the adolescent inpatients with psychiatric disorders have NSSI experience. Depression, gender were the risk factors for NSSI. Age at specific range had a high prevalence of NSSI.